2020
DOI: 10.1111/and.13548
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between visceral adiposity index and male infertility

Abstract: The visceral adiposity index (VAI), which is calculated by using parameters such as body mass index (BMI), waist circumference, triglyceride, and high‐density lipoprotein cholesterol, has been reported to be associated with visceral fat distribution and increased cardiometabolic risk. We aimed to investigate the relationship between the VAI and hormone profiles as well as semen analysis in male infertility. This retrospective study included 278 adult men that were admitted to the urology and endocrine outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Increased levels of leptin, estradiol (E2), insulin resistance (HOMA‐IR), and aromatase activity (testosterone to estradiol: T/E2), as well as decreasing levels of sex hormone‐binding globulin (SHBG) and testosterone (T), are possible hormonal alterations. High amounts of T in the testicles are required for sperm production and semen quality (Du Plessis et al, 2010; Turan & Öztekin, 2020). Obesity, on the other hand, is linked to lower total testosterone (TT) levels due to insulin resistance‐related reductions in the SHBG carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of leptin, estradiol (E2), insulin resistance (HOMA‐IR), and aromatase activity (testosterone to estradiol: T/E2), as well as decreasing levels of sex hormone‐binding globulin (SHBG) and testosterone (T), are possible hormonal alterations. High amounts of T in the testicles are required for sperm production and semen quality (Du Plessis et al, 2010; Turan & Öztekin, 2020). Obesity, on the other hand, is linked to lower total testosterone (TT) levels due to insulin resistance‐related reductions in the SHBG carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the increase in BMI may result in disruption of hormonal and seminal parameters [23,24]. Therefore, we considered BMI as a parameter that may affect the results in our study; however, we found that there was no difference in BMI between our groups.…”
Section: Discussionmentioning
confidence: 62%
“… 22 Furthermore, a study from Turkey found that high visceral adiposity was associated with decreased testosterone levels and testosterone/estradiol ratios, and VAI was also considered to be the strongest predictive marker of metabolic syndrome in females with polycystic ovary syndrome. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, a study from Turkey found that high visceral adiposity was associated with decreased testosterone levels and testosterone/ estradiol ratios, and VAI was also considered to be the strongest predictive marker of metabolic syndrome in females with polycystic ovary syndrome. 23,24 The association between VAI and CVD is considered to be related to the accumulation of adipokines, oxidative stress, and a proinflammatory milieu. 25 Now there are a lot of experimental and clinical evidence that atherosclerosis is a chronic inflammatory process involving many inflammatory cells and inflammatory mediators.…”
Section: Prediction Effect Of Vai Based On the Roc Curve On Cas In Di...mentioning
confidence: 99%